Analyzing Pump E-Warranty Registrations through Data Visualization: A Tableau-Based Approach - Riya Nilesh Borade; Prof. Sonali Ajay Mutha (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study explores the application of Tableau, a leading data visualization tool, to analyse and interpret e-warranty registration data for pump products. By transforming raw data into interactive and insightful visual dashboards, the research identifies key trends in warranty registrations, regional performance, and customer behaviour. The visualizations highlight patterns in branch efficiency and product reliability, providing a foundation for data-driven decision-making. The study demonstrates how Tableau can increase operational effectiveness, advance customer relationship strategies, and optimize warranty management systems across different regions and product types.
Keywords: Data Visualization; Tableau; E-Warranty System; Warranty Data Analysis; Business Intelligence; Pump Warranty Registrations; Dashboard Analytics; Regional Performance; Customer Insights; Interactive Visualizations; Warranty Management; Product Performance Analysis; Branch-wise Analysis; Predictive Analytics; Service Optimization